Modern Philological Knowledge: Anthropocentrism and Linguistic Identity - Petrovich Sedykh, Arkadiy; Nikolaevna Ivanishcheva, Olga; Vyacheslavovna Koreneva, Anastasiya; Vitalyevna Ryzhkova, Inna (International Journal of Engineering and Technology, 2018)
The article aims at analyzing the actual status of the "linguistic persona" category in the modern linguistic studies both in Russia and abroad. It is shown that the anthropocentric paradigm dominates in modern scientific knowledge. A linguistic persona is viewed as a certain type of linguistic identity functioning within the specific ways to exchange communicative information. The epistemology of scientific approaches and research concepts is regarded in the personological way. Universal and national and cultural ways of a personâ€™s verbalization are associated with a certain type of categorization of reality. The prospects of studying ways to verbalize the linguistic identity are viewed within the scope of the comprehensive analysis of communicative behavior based on the interdisciplinary approach. Using this method allows separating additional parameters of a linguistic persona of any type. The elements of the institutional linguistic persona are reviewed.Â